Influence of Leadership Style, Organizational Culture and Discipline Regarding the Performance of Employees of the Tax and Retribution Management Agency Batam City Region - Windayati, Diana; Sinta, Dwi (Zona Manajerial: Program Studi Manajemen (S1), 2023)
Abstract - The objective ot this study is to gather empirical evidence regarding the impact of leadership style, organizational culture and discipline on employee performance. The research was carried out at the Batam City Regional Tax and Levy Management Agency. The population of this research is all employees in the Batam City Regional Tax and Retribution Management Agency, involving all it’s employees as the population. A sample of 143 respondents was selected using the Slovin method. Multiple regression was employed as the testing method. The finding of the study reveal the collective impact of leadership style, organizational culture and discipline through the F-test, a calculated F value of 60,540 wth a significance level (sig) of 0.000. given the value 0.000 is less thean 0.05. Ho rejected and Ha accepted, indicating the significant of the regression model. In other word, it can be conclude that Leadership Style, Organizational Culture and Discipline collectively influence on Employee Performance.